2022
DOI: 10.2147/ijgm.s368344
|View full text |Cite
|
Sign up to set email alerts
|

CT Features of Stage IA Invasive Mucinous Adenocarcinoma of the Lung and Establishment of a Prediction Model

Abstract: Objective To investigate computed tomography (CT) features of stage IA invasive mucinous adenocarcinoma (IMA) of the lung and establish a predictive model. Methods Fifty-three lesions from 53 cases of stage IA IMA between January 2017 and December 2019 were examined, while 141 lesions from 141 cases of invasive non-mucinous lung adenocarcinoma (INMA) served as control cases. Univariate analysis was performed to compare differences in demographics and CT features between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…Notably, our study revealed an independent association between higher rad scores and IMA in the radiomics model. This observation can be explained by the heightened IMA heterogeneity, attributed to the abundant presence of mucin within the cytoplasm of IMA tumor cells and the aggressive nature of tumor neovascularization, closely associated with its malignant behavior [17]. The radiomics model achieved AUC values of 0.770 and 0.753 for the training and test sets, respectively, indicating higher diagnostic e ciency than that of the clinical model.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Notably, our study revealed an independent association between higher rad scores and IMA in the radiomics model. This observation can be explained by the heightened IMA heterogeneity, attributed to the abundant presence of mucin within the cytoplasm of IMA tumor cells and the aggressive nature of tumor neovascularization, closely associated with its malignant behavior [17]. The radiomics model achieved AUC values of 0.770 and 0.753 for the training and test sets, respectively, indicating higher diagnostic e ciency than that of the clinical model.…”
Section: Discussionmentioning
confidence: 97%
“…CT images currently provide limited information for differentiating between SPN-type IMA and non-mucinous LADC. Previous studies have suggested that certain CT features, including vacuolar signs, air bronchograms, and abnormal vascular changes, may help predict SPN-type IMA [16][17][18]. However, interpreting these features can be subjective and lack consistency or typicality.…”
mentioning
confidence: 99%
“…The diagnosis of IMA is challenging. Imaging findings can vary and be nonspecific, including consolidation of the lung parenchyma, nodules, honeycomb signs and ground-glass changes (13). However, common findings including irregular masses and absence of lung cancer signs.…”
Section: Discussionmentioning
confidence: 99%
“…The size of the lesion [expressed as the maximum diameter of the lesion (cm)], and consolidation-tumor-ratio (CTR) were measured according to the published literatures. 26,27…”
Section: Methodsmentioning
confidence: 99%